Cerium: An Unlikely Replacement of Dysprosium in High Performance Nd–Fe–B Permanent Magnets. (13th March 2015) - Pathak, Arjun K.; Khan, Mahmud; Gschneidner, Karl A.; McCallum, Ralph W.; Zhou, Lin; Sun, Kewei; Dennis, Kevin W.; Zhou, Chen; Pinkerton, Frederick E.; Kramer, Matthew J.; Pecharsky, Vitalij K.
<x xml:space="preserve">Abstract</x> Replacement of Dy and substitution of Nd in NdFeB‐based permanent magnets by Ce, the most abundant and lowest cost rare earth element, is important because Dy and Nd are costly and critical rare earth elements. The Ce, Co co‐doped alloys have excellent high‐temperature magnetic properties with an intrinsic coercivity being the highest known for T ≥ 453 K. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>